Transformasi User Interface Website OLU Mobile Apps: Optimalisasi UI/UX Berbasis Design Thinking - Firdaus Firmansyah; Ade Davy Wiranata; Ninda Baitza Maulana (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2024)
This research focuses on the transformation of Online Learning Uhamka (OLU) online learning website into a mobile application to overcome accessibility and display constraints that users often complain about on mobile devices. Through the application of the Design Thinking method which includes the stages of empathy, problem formulation, ideation, prototype development, and testing, this research seeks to design a responsive and user-friendly application. The UI/UX solution developed is based on user needs analysis, so that the application can be used comfortably on Android and iOS devices. By providing key features, such as assignment collection, attendance, and material access, the app is expected to improve the limitations of the website version and have a positive impact on users' learning effectiveness and experience in the context of online learning.